Experimental Investigations Into EDM Behaviours of En41b Using Copper and Brass Rotary Tubular Electrode. (2016) - Vincent, Nivin; Kumar, Arun B.
Abstract: In the present study, the performance parameters of EDM process are to be evaluated to achieve the feasibility in machining of nitride steel En41b which is extensively used in applications that required excellent resistance to wear and abrasion, e.g., connecting rods, small extruders, valve stems, dies, and gears. Here, the machining is done using rotary tubular copper and brass electrodes, in which the tool electrodes may have an additional rotary or orbiting motion, in addition to the servo-controlled feed. Taguchi's signal-to-noise ratio and grey relational analysis were applied in this work to improve the multi-response characteristics such as MRR and EWR on En41b steel and the optimum combination of control parameters such as current, gap voltage, pulse ON time and pulse OFF time were obtained.